Future Implementation of Ius Constituendum and Restorative Justice in the Criminal Justice System - Mashendra Mashendra; La Gurusi; La Ode Muhammad Karim (Jurnal Hukum Volkgeist, 2022)
The notion of restorative justice is presently implemented in the Indonesian criminal justice system through Law No. 11 of 2012, which oversees the juvenile court system. Future expansion of the application of restorative justice within the criminal justice system is a topic of discussion. As a research methodology, legal norm research is employed. Deductive reasoning is used to reach conclusions. On the basis of research findings, the Government and the DPR are expected to swiftly formulate guidelines for the implementation of the concept of restorative justice issued by the Criminal Justice Subsystem in laws and regulations, both in the form of laws and in the Draft Code of Criminal Procedure (RKUHAP) and the Draft Law – Criminal Law (RKUHP). The implementation or application of the concept of restorative justice in the resolution of criminal cases involving these offenders shall be governed by these rules.